2011
DOI: 10.1002/joc.2431
|View full text |Cite
|
Sign up to set email alerts
|

Connection between NAO, weather types and precipitation in León, Spain (1948–2008)

Abstract: ABSTRACT:The variability of winter precipitation in the west of the Iberian Peninsula is strongly affected by the North Atlantic Oscillation (NAO). This study focuses on identifying the relationship that exists between precipitation registered in the city of León (in northwestern Spain), the NAO index and the associated weather type during the same period. In order to achieve this objective, the prevailing weather type has been calculated for each day in León from January 1948 to March 2009, using the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 63 publications
4
42
0
Order By: Relevance
“…The Mean Precipitation, Percentage Contribution, and the Precipitation Intensity were first introduced by Trigo and DaCamara (2000) and where also measured by Fernández-González et al (2012), who in the same paper presented the Precipitation Efficiency index for the key series of Leon (NW Spain). In particular the Area of Influence index, to the best of our knowledge, was never presented before in literature.…”
Section: Precipitation Indicesmentioning
confidence: 99%
“…The Mean Precipitation, Percentage Contribution, and the Precipitation Intensity were first introduced by Trigo and DaCamara (2000) and where also measured by Fernández-González et al (2012), who in the same paper presented the Precipitation Efficiency index for the key series of Leon (NW Spain). In particular the Area of Influence index, to the best of our knowledge, was never presented before in literature.…”
Section: Precipitation Indicesmentioning
confidence: 99%
“…This paper has presented the results obtained by analyzing the association between daily weather types and hospital admissions due to respiratory diseases in Castilla-La Mancha along seven years (2000)(2001)(2002)(2003)(2004)(2005)(2006). The objective weather type classification by Lamb (1972) has been used, which has also recently been applied to rainfall patterns in the Iberian Peninsula (Fernandez-Gonzalez et al, 2012). Other authors like Hanna et al (2011) have found that certain synoptic air masses (dry tropical, transitional and extreme moist tropical) in conjunction with ambient ozone air levels were associated with increased asthma hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…The same classification has been used before to study rainfall patterns and air pollution in the Iberian Peninsula (Trigo and DaCamara, 2000;Calvo et al, 2012;Fernandez-Gonzalez et al, 2012).…”
Section: Daily Cwt Classificationmentioning
confidence: 99%
“…Following Trigo and DaCamara (2000) in their study for Portugal, this study does not have a separate class for unclassified days, but has opted for disseminating the fairly few cases with possible unclassified situations (< 2%) among the retained classes. This classification has been used previously for the Iberian Peninsula with a number of different applications, such as the study of lightning (Tomas et al, 2004), splash erosion , aerosol size distribution in precipitation events Calvo et al, 2012) or in studies on precipitation (Fernandez-Gonzalez et al, 2012).…”
Section: Measurement Equipmentmentioning
confidence: 99%